The Influence of Task-Based Instruction Towards the Students’ Ability in Writing Procedure Text at Grade Ten of SMA Tri Sukses Natar Lampung Selatan in Academic Year 2013-2014 - Tuti Rasminah (Bandar Lampung University (UBL), 2014)
The objective of This research was to find out The Influence of Task-Based Instruction Towards the Students’ Ability in Writing Procedure Text at Grade Tent of SMA Tri SuksesNatar. The data were collected by incorporating two pre-test and two post-test for experimental and control group. Treatment was administered for experimental group. While control group received traditional teaching. Data analysis was attempted using t-Test for two group design. Result indicated p-value 1% = 2,68 , 5% = 2.01, and t-value = 7,12. It is statistically significant. Therefore, null hyphothesis [Ho] was rejected and alternative hyphothesis [Ha] was accepted. These findings suggest that there is influence of Task-Based Instructions towards the students’ Ability in Writing procedure text at grade ten of SMA Tri SuksesNatar Lampung Selatan in Academic Year 2013-2014. It is suggested that the teachers should teach writing using Task-Based Instructions.